The genetic architecture of sporadic and multiple consecutive miscarriage - Triin Laisk (Nature Portfolio, 2020)
Miscarriage affects around 15% of clinically confirmed pregnancies. Here the authors carry out a large genome-wide association study for sporadic and multiple consecutive miscarriage and suggest links with placental biology.